Cidades inteligentes como estratégia para desenvolvimento de cidades sustentáveis : o caso da cidade de Búzios - Nascimento, Tatiana dos Santos Marcelino do (2018)
Cities by 2020 will house 70% of the world's population, accounting for 75% of the world's natural resources, 75% of energy consumption and 80% of greenhouse gas emissions. Because of this urban acceleration, there is an increasing need for resource availability and use, resulting in overburdened and unsustainable urban environments. It is increasingly difficult to maintain the frantic pace of production and sustainability of cities, so it is necessary to rethink a new model of urban development (FERREIRA, 2017). It is in this context that smart cities or smart cities appear, with the aim of making cities more livable, safe and productive, offering a better quality of life. This theme has influenced countless countries. It is a concept that is still forming, but it is a fact that it is related to technological, economic, political and socio-cultural transformations (HAUSER; BOCHI, 2017). Smart city also presents itself as a great challenge, since it presupposes a holistic and systemic vision of the urban space, besides the integration of diverse actors and sectors. In 2011, AMPLA / ENEL started the Búzios Intelligent City project, focused on energy efficiency in the region. He proposed that in the Balneario the smart grid or smart grid would use advanced digital solutions that would allow the electrical network to function in a similar way to the Internet. Connecting the traditional distribution network with modern solutions that would send energy, data and information that would feed the entire chain generating an efficient and sustainable energy network. The project had a term of 5 years with an investment of 54 million and reached countless stakerholders